The Impact of Social Media on Students' Language and Interaction in the Educational Environment - Adawiyah, Rabiyatul (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study discusses the impact of social media on student language and interaction in educational environments by reviewing four main focuses: (1) changes in student language due to social media use, (2) the influence of social media on learning outcomes, (3) student character and ethical values in the social media era, and (4) challenges and solutions in optimizing the educational use of social media. This study employs a descriptive-qualitative approach through literature review and/or observation of students' communication behavior in the context of learning and school socialization. The results show that the use of social media encourages a shift in student language towards a more concise, informal language, influenced by popular terms, abbreviations, and mixed languages, which has an impact on language habits in the classroom and in academic assignments. On the other hand, social media can positively contribute to learning outcomes through access to information, alternative learning resources, and collaboration, but it also has the potential to reduce concentration and discipline in learning and increase distraction if not controlled. In terms of character and ethics, social media poses challenges such as a decline in polite language, a tendency to imitate negative content, and an increased risk of cyberbullying, but it can also strengthen creativity, self-confidence, and the ability to express opinions if guided properly. These findings emphasize the need for strategies to strengthen digital literacy, instill communication ethics, and foster cooperation between schools and parents through device usage rules, guidance, and the planned use of social media as a learning tool.